Arbitrase Dalam Kepentingan Sengketa Merek di Indonesia - Novianti, Winda (Mutiara: Multidiciplinary Scientifict Journal, 2025)
Trademark rights are essential for commerce, providing product assurance and consumer guidance. Trademark disputes can cost companies financially and their brand image. Settlement of such disputes can be done through arbitration or institutions such as the Intellectual Property Rights Arbitration and Alternative Dispute Resolution Body (BAM HKI).So further in the research with normative methods in order to obtain the research objectives to determine the role of arbitration in trademark rights disputes.Arbitration is one of the steps in resolving trademark disputes outside the court. This method offers several benefits, such as less cost-effectiveness than litigation, confidentiality in the arbitration process, flexibility in choosing arbitrators and the settlement process, speed in reaching a decision, and decisions that are binding and enforceable in any court.